Police Decisions in a Rape Scenario: The Effect of Trauma Response, Forensic Evidence, Stranger–Perpetrators, and Rape Mythology - Franklin, Cortney A.; Bouffard, Leana A.; Goodson, Amanda; Garza, Alondra D. (Violence against women, 2023)
This study examined the direct effect of “classic rape” characteristics, and how they were moderated by rape myth endorsement, on the likelihood of arrest, perceived district attorney charge acceptance, and perceived suspect conviction using a formal rape disclosure among a sample of 468 police participants from a sizeable municipal law enforcement agency in one of the fifth largest and most diverse U.S. cities. A randomly assigned, between-subjects factorial vignette design was employed. Manipulations included stereotypical trauma response, forensic medical exam, and perpetrator type. Path modeling revealed statistically significant relations between stereotypical trauma response, forensic medical exam, perpetrator type, and the three outcome variables. Rape myth endorsement moderated the effect of manipulations on the dependent variables. Implications for research and policy are discussed.